SURVEY OF SUPPORT FOR PREGNANT AND PUERPERAL WOMEN WITH DEVELOPMENTAL DISABILITIES - Yuki Kanazawa; Mai Yamazaki (Journal of Maternity Care and Reproductive Health, 2021)
In Japan, no support system for mothers with developmental disabilities is currently in place. This study aimed to clarify the actual situation of support for pregnant and puerperal women with developmental disabilities in obstetrics and gynecology-related facilities. A self-administered questionnaire survey including free-form questions was distributed to 120 obstetrics and gynecology facilities in Prefecture A. The questionnaire responses were analyzed using descriptive statistics. The free descriptions were categorized and analyzed inductively. The valid response rate was 40.8% (n = 49). Twenty-five facilities reported dealing with pregnant and puerperal women with developmental disabilities, more than half of which provided support. None of the facilities had guidelines or pamphlets. Medical professionals felt a [lack of knowledge] and [difficulty in dealing with] support for mothers with developmental disabilities, and demanded the [construction of a support system].The present findings revealed that all facilities had problems with support systems and regional cooperation. Therefore, the establishment of a support method suitable for pregnant and puerperal women with developmental disabilities is needed.